Host plant frequency and secondary metabolites are concurrently associated with insect herbivory in a dominant riparian tree. (21st December 2018) - Moreira, Xoaquín; Galmán, Andrea; Francisco, Marta; Castagneyrol, Bastien; Abdala-Roberts, Luis
Abstract : Herbivory is strongly influenced by different sources of plant variation, from traits such as secondary metabolites to features associated with population- and community-level variation. However, most studies have assessed the influence of these drivers in isolation. We conducted a large-scale study to evaluate the associations between multiple types of plant-based variation and insect leaf herbivory in alder ( Alnus glutinosa ) trees sampled in riparian forests throughout northwestern Spain. We assessed the associations between insect leaf herbivory and alder mean production of leaf secondary metabolites (phenolic compounds), variation among neighbouring alder trees in leaf phenolics and community-related features including alder relative size and frequency and tree species phylogenetic diversity. Structural equation modelling indicated that increasing concentrations of alder leaf flavonoids (but not other types of phenolic compounds) and increasing variation in phenolics among neighbouring alders were both significantly negatively associated with herbivory. In addition, increasing relative frequency of alder was positively associated with leaf damage, whereas the size of alders relative to other trees and phylogenetic diversity were not significantly associated with herbivory. These results demonstrate the concurrent and independent influences of different sources of plant-based variation on insect herbivory and argue for further future work simultaneously addressing multiple plant-based bottom-up controls.